2011
DOI: 10.1111/j.1526-4637.2011.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Back Pain After Percutaneous Endoscopic Lumbar Discectomy and Annuloplasty for Lumbar Disc Herniation: A Prospective Study

Abstract: PELDA can relieve back pain as well as leg pain through direct decompression and thermal ablation of the annular defect. Disc degeneration can be expected to influence clinical outcomes following PELDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
0
33
0
1
Order By: Relevance
“…PELD recurrence rates are reported to range from 0% to 7.4%. 2,18,23,[29][30][31] Recurrence rates after open discectomy have been reported to range from 1% to 21%. 32,33 Several studies showed no difference in recurrence rates between PELD and open discectomy.…”
Section: Unsuccessful Percutaneous Endoscopic Lumbar Discectomymentioning
confidence: 99%
“…PELD recurrence rates are reported to range from 0% to 7.4%. 2,18,23,[29][30][31] Recurrence rates after open discectomy have been reported to range from 1% to 21%. 32,33 Several studies showed no difference in recurrence rates between PELD and open discectomy.…”
Section: Unsuccessful Percutaneous Endoscopic Lumbar Discectomymentioning
confidence: 99%
“…2,6,10,13,19,24,25,29,36,46,51,53,57,60,62,64 Percutaneous discectomy entails placing a sheath directly into the disc space via a transforaminal approach, extraforaminal approach, or interlaminar approach and then using a suction/debrider or chemical injection to remove the disc. 1,11,12,23,30,37,44,50 To assess the risk of bias for each study, 3 reviewers (M.F.S., J.J.X., and E.Y.T.) independently investigated the individual studies and used The Cochrane Collaboration's tool for assessing risk of bias.…”
Section: Data Collectionmentioning
confidence: 99%
“…With the development of minimally invasive endoscopic methods in spine surgery, a number of techniques have recently been developed that are applicable in the treatment of lumbar disc herniation. [1][2][3][4][5][6] The current trend of evolution lumbar spinal surgery has been toward endoscopic discectomy, which is a minimally invasive treatments aimed at removing nuclear material and decompression the nerve through devices were inserted percutaneous into intervertebral discs. [7,8] Endoscopic discectomy is a well-established technique for nerve decompression by transforaminal to access the disc space, and transforaminal endoscopic lumbar discectomy has become population for its advantages and matured with time.…”
Section: Introductionmentioning
confidence: 99%
“…[17] There were many studies of endoscopic discectomy and showed good clinical results, which has the major advantages of sufficient decompression with no retraction on the nerve ganglion, less postoperative pain and earlier functional recovery. [2,18,19] Degenerative changes and disc herniation are commonly found in lumbar spine and correlate with age, but only some people been involved one vertebral body and one disc level. [12,[20][21][22]15] For those who had multiple level disc herniation is greatest in the age group of the population, and the most common cause of leg pain is disc prolapse which majorities at L4/L5, L5/S1, or L3/L4 levels.…”
Section: Introductionmentioning
confidence: 99%